2006
DOI: 10.2164/jandrol.05073
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Human Semen Characteristics and Sperm Apoptosis: A Pilot Study

Abstract: This work was undertaken to explore the association between human semen characteristics and apoptosis in ejaculated sperm. We collected semen samples from 23 consecutive male patients who presented to the Andrology Laboratory at Massachusetts General Hospital (MGH) for routine semen analysis. Sperm concentration and motility were measured using computer-assisted sperm analysis. Morphology was assessed using Tygerberg strict criteria. The DNA diffusion assay was used to assess the percentage of apoptosis in eja… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
35
1
2

Year Published

2008
2008
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(48 citation statements)
references
References 37 publications
8
35
1
2
Order By: Relevance
“…Zini et al [39] demonstrated negative correlations between sperm DNA integrity and sperm quality in partners of couples attending IVF clinics. Additionally, in a small cohort of patients consulting for infertility investigation, prospective analyzes showed that both sperm motility and sperm morphology were inversely correlated to the rate of nuclear DNA fragmentation [10][11][12]36]. These results corroborated with our findings and suggested that sperm motility and morphology defects may be in part due to a reduction of sperm DNA integrity which can be promutagenic and can adversely affect fetal outcome after IVF and has lifelong implications on health of child [34].…”
Section: Discussionsupporting
confidence: 88%
“…Zini et al [39] demonstrated negative correlations between sperm DNA integrity and sperm quality in partners of couples attending IVF clinics. Additionally, in a small cohort of patients consulting for infertility investigation, prospective analyzes showed that both sperm motility and sperm morphology were inversely correlated to the rate of nuclear DNA fragmentation [10][11][12]36]. These results corroborated with our findings and suggested that sperm motility and morphology defects may be in part due to a reduction of sperm DNA integrity which can be promutagenic and can adversely affect fetal outcome after IVF and has lifelong implications on health of child [34].…”
Section: Discussionsupporting
confidence: 88%
“…A significant negative relationship between the proportions of apoptotic sperm and the proportions of sperm with normal morphology in semen applying the Tygerberg's strict criteria (Kruger et al, 1988) has been reported (Chen et al, 2006). In another study normal sperm morphology assessed in the swim-up preparations correlated negatively with chromatin fragmentation only in teratozoospermic semen samples but not in normospermic ones as determined by the WHO 1992 criteria (Muratori et al, 2003).…”
Section: Function and Relevance Of Caspase Activation In Spermatozoa mentioning
confidence: 93%
“…Several studies investigated the relationship between sperm morphology and apoptosis (Aziz et al, 2007;Chen et al, 2006;Gandini et al, 2000;Ricci et al, 2002;Sakkas et al, 2002;Shen et al, 2002;Siddighi et al, 2004). The design of these studies might not have facilitated the accurate distinction between moribund or necrotic sperm and motile sperm expressing apoptotic markers.…”
Section: Function and Relevance Of Caspase Activation In Spermatozoa mentioning
confidence: 99%
See 1 more Smart Citation
“…In infertile patients, an increased incidence of chromosome anomalies [Carrell 2008;Sarrate et al 2010], and parallel elevated percentages of apoptosis in spermatozoa have been described [Tesarik et al 1998;Carrell et al 2003;Chen et al 2006]. The chromosome anomalies are related to synapsis abnormalities, and recombination and segregation in germ cells [Topping et al 2006].…”
Section: Introductionmentioning
confidence: 99%